(3GdhMOI GdbQBfjI (B/s (3OQGSI JMdjdjI ebGQfI (B.s - (3NhLI, eMeO eMehOs ((3GdQjGV(B:s (3OGQ cfhR ETHjdjG ddfTQ hGdJhRjY,s, 2010)
(3GSJYQV GdHGMK aj CWQhMJg GdhMOI GdbQBfjI Hjf ShQI GdaGJMI hShQ GdbQBf haj GdCbSGe GdbQBfjI hhLg UdI GdWhd aj GdJhQGI hGdeJjf aj GdRHhQ hGdeKGfj aj GdEfLjd hhLg JejR GdeaUd Yf GdCbSGe GdKdGKI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI Ce OQeGf GdESdGejI, cdjI CUhd GdOjf, bSe GdJaSjQ hYdhe GdbQBf, (B2005.s
(3eJGMI fSNI Ydi Tcd bQU edjRQ(B.s
Keywords: (3GdbQBfs -- (3eHGMK YGeIs